ORDINANCE NO. ORDINANCE REGULATING SMOKING IN ENCLOSED PUBLIC PLACES, PLACES OF EMPLOYMENT, AND EDUCATIONAL AND HEALTH FACILITIES, REQUIRING RESTARANTS TO SMOKING SECTIONS (Tufts Archival Research Center, 2007)
Ordinance in Dade County regulating smoking in enclosed public places, places of employment, and educational and health facilities. Highlights exceptions laid out for smoker accommodation.